Friction and Wear of MoO3/Graphene Oxide Modified Glass Fiber Reinforced Epoxy Nanocomposites. Issue 8 (25th June 2019) - He, Yuxin; Chen, Qiuyu; Liu, Hu; Zhang, Li; Wu, Dongyang; Lu, Chang; OuYang, Wei; Jiang, Danfeng; Wu, Mingfang; Zhang, Jiaoxia; Li, Yingchun; Fan, Jincheng; et al.
Abstract: In order to further improve the tribological performance of glass fiber reinforced epoxy (GF/EP) composites, highly flexible, binder‐free, molybdenum trioxide MoO3 nanobelt/graphene oxide (GO) film ( f ‐MoO3 ‐GO) is prepared by a hydrothermal method. Herein, f ‐MoO3 ‐GO is adopted to modify GF/EP composites prepared through the vacuum‐assisted resin transfer molding method. The neat GF/EP and MoO3 ‐GO modified GF/EP composites are also fabricated for comparison. The tribological performance is performed using a ball‐on‐disc ("steel‐on‐polymer") configuration under a dry sliding condition. The coefficient of friction is reduced from 0.61 for neat GF/EP composites down to 0.23 for f ‐MoO3 ‐GO modified GF/EP ( f ‐MoO3 ‐GO/GF/EP) composites and the anti‐wear performance is improved by more than four times. The worn surface morphological observation for the composite samples is used to explain the possible wear micro‐mechanisms. The wear reducing effect of the f ‐MoO3 ‐GO/GF/EP composites can be assigned to the increased self‐lubricating effect of f ‐MoO3 ‐GO. With the combined advantageous properties of the used individual components, these unique composites can be used for many other applications. Abstract : MoO3 nanobelt/graphene oxide film (   f ‐MoO3 ‐GO) is prepared to modify the tribological performance of the GF/EP composites. Compared to neat GF/EP composites, the coefficient of friction and wear rate of the f ‐MoO3 ‐GO/GF/EP composites are reduced. The worn surface morphological observation for the composite samples is used to explain the possible wear micro‐mechanisms.